Enhanced Detection of Human Immunodeficiency Virus Type 1 (HIV-1) Nef-Specific T Cells Recognizing Multiple Variants in Early HIV-1 Infection - Malhotra, Uma (American Society for Microbiology, 2007)
A human immunodeficiency virus (HIV)-preventive vaccine will likely need to induce broad immunity that can recognize antigens expressed within circulating strains. To understand the potentially relevant responses that T-cell based vaccines should elicit, we examined the ability of T cells from early infected persons to recognize a broad spectrum of potential T-cell epitopes (PTE) expressed by the products encoded by the HIV type 1 (HIV-1) nef gene, which is commonly included in candidate vaccines. T cells were evaluated for gamma interferon (IFN-γ) secretion using two peptide panels: subtype B consensus (CON) peptides and a novel peptide panel providing 70% coverage of PTE in subtype B HIV-1 Nef. Eighteen of 23 subjects’ T cells recognized HIV-1 Nef. In one subject, Nef-specific T cells were detected with the PTE but not with the CON peptides. The greatest frequency of responses spanned Nef amino acids 65 to 103 and 113 to 147, with multiple epitope variants being recognized. Detection of both the epitope domain number and the response magnitude was enhanced using the PTE peptides. On average, we detected 2.7 epitope domains with the PTE peptides versus 1.7 domains with the CON peptides (P = 0.0034). The average response magnitude was 2,169 spot-forming cells (SFC)/10(6) peripheral blood mononuclear cells (PBMC) with the PTE peptides versus 1,010 SFC/10(6) PBMC with CON peptides (P = 0.0046). During early HIV-1 infection, Nef-specific T cells capable of recognizing multiple variants are commonly induced, and these responses are readily detected with the PTE peptide panel. Our findings suggest that Nef responses induced by a given vaccine strain before HIV-1 exposure may be sufficiently broad to recognize most variants within subtype B HIV-1.